Characteristics of Blockchain Technology In Educational Development - Kurniawan, Rano; Duwita oktaviani (Blockchain Frontier Technology, 2022)
The worldwide education implementation process has not been able to keep up with contemporary events. The education sector is now dealing with a number of issues, including the problem of verification and the presence of a third party in the management of certificates, which are micro and macro outputs of a company's learning process. The existence of a beacon of Blockchain technology, which is frequently referred to as a revolutionary solution to the current educational debate. In the education business, the merger of education with blockchain technology will usher in a new era. There are numerous reasons for this solution, but I don't believe they are sufficient to describe the features of blockchain in detail from the perspective of education utilizing blockchain, which examines the presence of blockchain for education based on scientific investigations. These features of blockchain will be highly valuable as a literary platform for scholars who will begin fundamental research and applications that will lead to blockchain for education in the future. Aside from that, there will be recommended solutions in the form of a framework for the cost, storage space, and speed of blockchain technology. As a result, this research can also serve as a basis for the new blockchain as a predecessor of technology-based governance blockchains.